2011
DOI: 10.1159/000329510
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Modulates the Cytotoxic Effects of Paclitaxel

Abstract: Background: Paclitaxel is a microtubule-stabilizing drug known to cause mitotic G2/M arrest and apoptosis. It also increases the generation of reactive oxygen species (ROS) known to be involved in both apoptotic and necrotic cell death. Antioxidants, such as N-acetylcysteine (NAC), prevent the deleterious effects of ROS and modulate the regulation of apoptotic-linked cellular proteins. Methods: A549 human adenocarcinoma alveolar epithelial cells were treated with 5.0 mM NAC, 1.0 µM paclitaxel, or co-incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Recently, it has been demonstrated that ROS can induce autophagy (24). Early studies have shown that paclitaxel can induce the generation of ROS in several cancer cell lines, and that this induction of ROS is involved in paclitaxel-induced apoptosis (21)(22)(23). Our study also demonstrated that paclitaxel induced ROS generation in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Recently, it has been demonstrated that ROS can induce autophagy (24). Early studies have shown that paclitaxel can induce the generation of ROS in several cancer cell lines, and that this induction of ROS is involved in paclitaxel-induced apoptosis (21)(22)(23). Our study also demonstrated that paclitaxel induced ROS generation in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 73%
“…As paclitaxel can trigger the generation of intracellular ROS in many cancer cell lines (21-23), we next investigated whether ROS was elevated in HEC-1A and JEC cells following paclitaxel exposure. Since DCFH-DA was often used to assess paclitaxel-induced ROS in previous studies (21,23), we used DCFH-DA to measure the intracellular levels of ROS in our study. DCFH-DA can diffuse into cells through the cell membrane, and subsequently become hydrolyzed to non-fluorescent DCFH.…”
Section: Inhibition Of Autophagy Increases Paclitaxel-induced Cell Dementioning
confidence: 99%
“…In general, induction of oxidative stress as a mechanism that may contribute to the antineoplastic effect of several chemotherapeutic agents has been gaining acceptance [39]. Antioxidants, such as N-acetylcysteine, have been shown to inhibit both paclitaxel-evoked decreases in cell viability and increases in intracellular levels of ROS and apoptosis, [30]. N-acetylcysteine has been reported to prevent completely paclitaxel-evoked mechanical hypersensitivity [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, GJG suppresses the release of pain-transmitting substance, increases NO production mediated by bradykinin B2 receptor and muscarinic acetylcholine receptor [15] and reduces reactive oxygen species production [25]. Because PTX therapy accumulates of hydrogen peroxide [26, 27] and antioxidant such as N-acetylcysteine can alter the cytotoxicity of PTX [28] and PTX-induced mechanical hyperalgesia [29], it is presumed that antioxidant action of GJG is likely be involved in protecting PTX-inducing neural damage. Materazzi et al demonstrated that an antioxidant, glutathione, suppresses PTX-induced expression of TRPV4 in the sensory nerve [30], which strongly supports our presumption.…”
Section: Discussionmentioning
confidence: 99%